Surface-treated metal materials and joints

The surface-treated metal material with a controlled silane coating addresses the challenges of adhesive bonding by enhancing adhesion strength and durability, particularly in high-temperature and humid environments.

JP7648820B2Active Publication Date: 2025-03-18KOBE STEEL LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2024020418
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2023-05-15
Filing Date
2024-02-14
Publication Date
2025-03-18
Estimated Expiration
2044-02-14

AI Technical Summary

Technical Problem

Adhesive bonding technologies face challenges with long-term strength reliability, particularly in environments with high temperatures and humidity, where the adhesion between metal and resin tends to decrease, leading to corrosion and peeling issues.

Method used

A surface-treated metal material with a silane coating is developed, where the silane coating is formed on at least a part of the metal substrate, and the surface roughness and absorption spectrum are controlled to enhance adhesion strength and durability.

Benefits of technology

The surface-treated metal material achieves excellent adhesive strength and durability with resins, even in harsh environments, by ensuring strong bonding between the silane coating and the adhesive resin layer.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007648820000002
    Figure 0007648820000002
  • Figure 0007648820000003
    Figure 0007648820000003
  • Figure 0007648820000004
    Figure 0007648820000004
Patent Text Reader

Abstract

To provide a surface-treated metal used for adhesion bonding and capable of further improving bond durability, and a bonded body including the surface-treated metal.SOLUTION: A surface-treated metal includes a silane film provided on at least a part of the surface of a metal base material. When irradiating the surface of the silane film with parallel polarization having an incident angle of 75° to measure an absorption spectrum by Fourier transformation infrared spectroscopy, an absorption peak is included in a wave number range of 1250 (cm-1) or more and 1150 (cm-1) or less, and when measuring a surface roughness in a measuring range of 1 mm×1 mm in three arbitrary places by a laser beam microscope on the surface of the silane film, an aspect ratio is 0.5 or more.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a surface-treated metal material and a joined body including the surface-treated metal material. [Background technology]

[0002] In the field of transportation such as automobiles, ships and aircraft, adhesive joining is used as a joining technique between dissimilar materials such as steel and lightweight materials (aluminum alloys, titanium alloys, carbon fibers, etc.) from the viewpoint of weight reduction. In addition, adhesive joining is attracting attention as an alternative technique to welding from the viewpoint of improving productivity and workability in order to address on-site issues such as a lack of successors for welding, skill transfer, and improving the work environment.

[0003] On the other hand, adhesive bonding has problems with strength reliability during long-term use, and it is known that adhesive bonding is more likely to experience strength degradation than welding or bolting in high temperature, high humidity environments, and environments where stresses such as fatigue or creep act in combination. In adhesive bonding, the adhesion between the adhesive and the metal to be adhered is important, and if the adhesion between the metal material surface and the adhesive is insufficient, water will penetrate into the interface between the metal and the resin. As a result, corrosion of the metal surface progresses and peeling occurs from the interface between the two, resulting in a significant decrease in adhesive strength. Therefore, it is necessary to prevent water from penetrating the adhesive interface by increasing the adhesion between the metal and the adhesive resin, and to modify the surface of the metal material to adjust the surface condition to be suitable for adhesion so that the state of the metal surface does not easily change even if water penetrates.

[0004] In order to solve the above problems, various surface treatment techniques have been proposed. For example, Patent Document 1 discloses an aqueous composition containing tetraalkyl silicate or its monomeric or oligomeric hydrolysis product and a hydrated oxide sol such as silica sol. By treating metal materials such as aluminum, steel, and titanium with the aqueous composition, the initial adhesion and long-term stability of the adhesion of a coating film such as an adhesive formed thereon can be improved. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] Special Publication No. 10-510307 Summary of the Invention [Problem to be solved by the invention]

[0006] However, even when the surface treatment technology described in Patent Document 1 is used, the adhesive strength with the resin such as the adhesive is significantly reduced by a long-term wet deterioration test, and therefore the required adhesive durability cannot be obtained.

[0007] The present invention has been made in consideration of such problems, and has an object to provide a surface-treated metal material that has excellent adhesive strength with resins such as adhesives and can further improve the adhesive durability with resins, and a joined body including this surface-treated metal material. [Means for solving the problem]

[0008] The above object of the present invention can be achieved by the following configuration [1] relating to a surface-treated metal material.

[0009] [1] A surface-treated metal material having a silane coating on at least a portion of the surface of a metal substrate, When parallel polarized light having an incident angle of 75° was incident on the surface of the silane coating, the absorption spectrum was measured by Fourier transform infrared spectroscopy, and the absorption spectrum was 1250 (cm -1 ) or more 1150(cm -1 ) or less wave number region, A surface-treated metal material characterized in that, when the surface roughness of the surface of the silane coating is measured using a laser microscope over a measurement area of ​​1 mm x 1 mm at any three points on the surface of the silane coating, the aspect ratio is 0.5 or more.

[0010] Furthermore, preferred embodiments of the present invention relating to a surface-treated metal material relate to the following [2] and [3].

[0011] [2] The surface-treated metal material according to [1], characterized in that it has an adhesive resin layer on the surface of the silane coating.

[0012] [3] The absorbance at the absorption peak is 0.003 or more. A surface-treated metal material according to [1] or [2].

[0013] The above object of the present invention can be achieved by the following configurations [4] and [5] relating to a bonded body.

[0014] [4] A joined body including the surface-treated metal material according to any one of [1] to [3], The first member and the second member are joined via an adhesive resin layer, One of the first member and the second member is the surface-treated metal material, A bonded body, characterized in that the silane coating of the surface-treated metal material and the adhesive resin layer are bonded to each other.

[0015] [5] A joined body including the surface-treated metal material according to any one of [1] to [3], The first member and the second member are joined via an adhesive resin layer, the first member and the second member are both surface-treated metal materials each having a metal base material made of the same or different metal materials, A bonded body, characterized in that the silane coating of the first member and the silane coating of the second member are bonded together by the adhesive resin layer. Effect of the Invention

[0016] According to the present invention, it is possible to provide a surface-treated metal material that has excellent adhesive strength with a resin such as an adhesive and can further improve the adhesive durability with the resin, and a joined body including this surface-treated metal material. [Brief description of the drawings]

[0017] [Figure 1] FIG. 1 is a graph showing an absorption spectrum, with the vertical axis representing absorbance and the horizontal axis representing wave number. [Figure 2A] FIG. 2A is a side view showing the shape of the bonded body. [Figure 2B] FIG. 2B is a plan view showing the shape of the bonded body. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0018] The present inventors have conducted extensive research into metal materials that can improve the adhesive strength and durability with resin, even for poorly adhesive metal materials such as stainless steel and titanium. As a result, they have found that the above problems can be solved by appropriately controlling the absorption spectrum and surface roughness on the surface of the silane coating. The surface-treated metal material according to the embodiment of the present invention will be described in detail below.

[0019] [Surface-treated metal materials] The surface-treated metal material according to this embodiment is a metal substrate having a silane coating formed on at least a portion of the surface thereof. The metal substrate and the silane coating will be described in more detail below.

[0020] <Metal base material> The metal substrate is not particularly limited in type or shape as long as it is a member made of metal. Examples of the metal include steel plate, various plated steel plate, pure aluminum or aluminum alloy, pure titanium or titanium alloy, stainless steel, copper or copper alloy, etc. In particular, known aluminum alloys such as Al-Mg alloys, Al-Mg-Si alloys, Al-Zn-Mg alloys, Al-Si alloys, and Al-Cu alloys can be used. Known titanium alloys such as α-titanium alloys, β-titanium alloys, and α+β-titanium alloys can be used. Known stainless steels such as austenitic stainless steels, ferritic stainless steels, martensitic stainless steels, and duplex stainless steels can be used.

[0021] <Silane film> The silane coating is provided on at least a part of the surface of the substrate, and specifically, is a surface treatment coating containing an organic silane compound. The silane coating containing a silane compound has excellent bonding strength with an adhesive and excellent corrosion resistance, so that the silane coating can maintain excellent bonding strength when adhesively bonded to another member.

[0022] The silane film can be formed, for example, by applying an aqueous solution containing silicon oxide to the surface of the substrate. Silicon oxide is activated by dissolving it in an aqueous solution, and can self-polymerize through a sol-gel reaction. In addition, a natural oxide film is formed on the substrate made of titanium or a titanium alloy. Therefore, by applying an aqueous solution of silicon oxide onto the oxide film on the surface of the substrate, the titanium oxide film reacts with the silicon oxide, and the silicon oxide also polymerizes with itself, so that a silane film having excellent bonding strength with the substrate can be formed in a desired region on the surface of the substrate.

[0023] In addition, the silane film has high mutual solubility with machine oils such as processing oil and press oil, and organic compounds such as adhesives, and therefore has excellent bonding properties with adhesives. Furthermore, the silane film can mitigate the effects of machine oils such as processing oil and press oil even if they are attached, so it can prevent a decrease in adhesion durability due to oil application and can obtain excellent corrosion resistance.

[0024] (Absorption spectrum by Fourier transform infrared spectroscopy) When a silane film is formed on the surface of a metal substrate, a bond between silicon and oxygen is necessarily formed in the region where the silane film is formed. In this embodiment, as an indicator of whether or not a silane film is certainly formed, a method is used in which parallel polarized light with an incident angle of 75° is incident on the surface of the silane film and an absorption spectrum is measured by Fourier transform infrared spectroscopy (FT-IR).

[0025] FIG. 1 is a graph showing an absorption spectrum with the absorbance on the vertical axis and the wave number on the horizontal axis. The silicon-oxygen bond is at 1250 (cm -1 ) or more 1150(cm -1 1.) In the wave number region below, there is an absorption peak as indicated by the arrow in Fig. 1. Therefore, by observing the presence or absence of an absorption peak in the above wave number region, it is possible to determine whether or not a silane film has been formed.

[0026] In addition, if the absorbance at the absorption peak is 0.003 or more, the presence or absence of a silane film can be determined more reliably. -1 ) or more 1150(cm -1 ) or less, the absorbance of the peak is preferably 0.003 or more.

[0027] (Surface roughness) If the surface shape of the metal substrate is uniformly (uniformly) rough, the metal treatment solution is uniformly held on the surface of the metal substrate during surface treatment to form a silane film, and as a result, a silane film is formed with a uniform amount of film, and a silane film with excellent performance can be obtained. If the surface shape of the metal substrate is uneven, the metal treatment solution will remain in some places, for example, in deep grooves, and the silane film will become thick only in the grooves, making it impossible to obtain a silane film with good performance. In addition, if the silane film is formed with a uniform thickness, when stress is applied to the adhesive joint, the stress applied to the interface can be uniformly distributed. In this way, by reducing the force applied per unit area, the bonding strength can be stabilized as a result. Note that the thickness of the silane film of the surface-treated metal material according to this embodiment is several nm, so the surface shape of the metal substrate is also similarly expressed on the surface of the surface-treated metal material. Therefore, in this embodiment, it is specified by the surface roughness on the surface of the surface-treated metal material.

[0028] The surface roughness of the surface-treated metal material can be specified using the surface roughness specified in ISO 25178. In this embodiment, the presence or absence of a silane coating having excellent performance is judged based on Str (aspect ratio of surface properties) obtained by measuring the surface roughness by a laser microscope in a measurement range of 1 mm x 1 mm at any three points on the surface of the silane coating. Str takes a value of 0 to 1, and when it is close to 0, it indicates that there are streaks and the surface shape is unevenly rough. On the other hand, when Str is close to 1, it indicates that the surface shape is uniformly rough without depending on the direction, so in this embodiment, Str is preferably close to 1.

[0029] If the aspect ratio is less than 0.5, the surface shape of the metal substrate becomes significantly biased, and it is not possible to form a silane coating with a uniform thickness, making it impossible to obtain a silane coating with excellent performance. Therefore, the aspect ratio obtained by the above measurement method is 0.5 or more, preferably 0.7 or more, and more preferably 0.8 or more.

[0030] As a method for uniformly roughening the surface of the surface-treated metal material, for example, a method of performing a blast treatment on the metal substrate can be mentioned. Specifically, the aspect ratio Str can be adjusted by selecting the type of blast material.

[0031] The surface-treated metal material according to the present embodiment configured as described above has a silane coating provided on at least a part of the surface of a metal substrate, and the absorption spectrum and aspect ratio of the surface of the silane coating are specified, resulting in a silane coating that has excellent adhesion to the metal substrate and durability.

[0032] In addition, the silane coating has high mutual solubility with machine oils such as processing oil and press oil, and organic compounds such as adhesives, and therefore has excellent bonding properties with adhesives. Furthermore, the silane coating can mitigate the effects of machine oils such as processing oil and press oil even if they are attached, so it is possible to prevent a decrease in adhesion durability due to oil application and obtain excellent corrosion resistance. Therefore, when the surface-treated metal material obtained by the manufacturing method according to this embodiment is adhesively bonded to another member, excellent bonding strength can be maintained for a long period of time.

[0033] <Adhesive resin layer> The surface-treated metal material according to the present embodiment may further have an adhesive resin layer on the surface of the silane coating. As described above, by having an adhesive resin layer on the surface of the silane coating, which has excellent adhesion to an adhesive and durability, the process of adhesively bonding the surface-treated metal material according to the present embodiment to a similar surface-treated metal material or other members can be simplified.

[0034] The method for forming an adhesive resin layer on at least a portion of the surface of the silane coating is not particularly limited, but for example, an adhesive sheet made in advance from an adhesive resin material may be attached to the surface of the silane coating, or the adhesive resin material may be sprayed or applied to the surface of the silane coating.

[0035] In the present invention, the resin constituting the adhesive resin layer is not particularly limited, and adhesive resins that have been used in the past when joining titanium or titanium alloy materials, such as epoxy resins, urethane resins, nitrile resins, nylon resins, acrylic resins, etc., can be used. The thickness of the adhesive resin layer is also not particularly limited, but from the viewpoint of improving the adhesive strength, it is preferably 10 to 500 μm, more preferably 50 to 400 μm.

[0036] [Method of manufacturing surface-treated metal materials] The surface-treated metal material according to this embodiment can be produced, for example, as follows.

[0037] <Blast treatment process> First, a blasting process is performed on at least a part of the surface of the metal substrate. Specifically, abrasive grains for blasting or a solution containing abrasive grains is projected onto the surface at high speed using compressed air, a motor, or the like. This removes contaminants, deposits, and oxide films present on the surface of the metal substrate, and cleans it, while forming an uneven shape on the surface region of the metal substrate, allowing the aspect ratio to be adjusted.

[0038] (Type of blasting) The type of blasting in the blasting process is not particularly limited, and either a dry blasting method or a wet blasting method may be used, and the same effect can be obtained using either method. For example, the dry blasting method is preferable from an economical point of view because the equipment is small and versatile. In addition, the wet blasting method is preferable from the viewpoint of dust prevention and processing stability because the heat input to the surface of the metal substrate 1 is small and the abrasive grains can be suppressed from remaining. In addition, the type of abrasive grains is not particularly limited, and commercially available abrasive grains can be used.

[0039] <Adhesion process> Next, a metal treatment solution containing a silane compound is applied to the surface area of ​​the metal base material that has been subjected to the blast treatment. In the application step, the metal base material is coated with a suitable amount of the main component, which is mainly the silane compound, on the surface of the metal base material, and examples of the application method include spraying, showering, roll coating, brush application, and immersion treatment. Specific examples of the metal treatment solution will be described later.

[0040] <Drying process> Thereafter, the solvent is evaporated from the metal treatment solution applied to the surface of the metal substrate, and the metal substrate is dried to promote the reaction between the silane compound and the oxide film, and the polymerization between the silane compounds themselves. As a result, a silane film is formed on at least a part of the surface of the metal substrate, and a surface-treated metal material can be produced. The drying temperature is not particularly limited, but for example, a temperature of about 50 to 100°C is preferable because it provides a good balance between productivity and energy consumption. In addition, in order to improve the soundness of the silane film and maximize the adhesive effect between the substrate and the silane film, the step of applying the metal treatment solution to the surface of the substrate and the step of drying the surface of the substrate may be repeated two to three times.

[0041] <Adhesive resin layer formation process> The surface-treated metal material according to this embodiment preferably further has an adhesive resin layer on the surface. Specifically, after the drying step, an adhesive resin layer is formed on the surface of the silane coating. As described above, by forming an adhesive resin layer on the surface of the silane coating, which has excellent adhesion to adhesives and durability, the process of adhesively bonding the surface-treated metal material to a similar surface-treated metal material or other members can be simplified.

[0042] The method for forming the adhesive resin layer is not particularly limited, but for example, an adhesive sheet made in advance from an adhesive resin material may be attached to the surface of the silane coating, or the adhesive resin material may be sprayed or applied to the surface of the silane coating.

[0043] In the present invention, the resin constituting the adhesive resin layer is not particularly limited, and adhesive resins that have been used in the past when joining titanium or titanium alloy materials, such as epoxy resins, urethane resins, nitrile resins, nylon resins, acrylic resins, etc., can be used. The thickness of the adhesive resin layer is also not particularly limited, but from the viewpoint of improving the adhesive strength, it is preferably 10 to 500 μm, more preferably 50 to 400 μm.

[0044] The metal treatment solution for forming the silane film will be described below with specific examples.

[0045] (Metal treatment solution) The metal treatment solution may be any solution containing a silane compound, and may be, for example, a solvent containing 50% by mass to 99.99% by mass of water and 0% by mass to 50% by mass of an organic solvent. The mass of water relative to the total mass of the solution is more preferably 50% by mass to 99.95% by mass. From the viewpoint of reducing volatile organic compounds (VOCs) and reducing the risk of explosion, it is preferable that the main component of the solvent is water. However, in order to reduce the surface tension of the metal treatment solution, improve water wettability and coatability, and improve the drying speed, the following organic solvents may be included.

[0046] When an organic solvent is used, various water-soluble solvents such as various alcohols and polyethers, for example, methanol, ethanol, propyl alcohol, butanol (including isomers), glycol solvents and their ethers, can be used.

[0047] The metal treatment solution contains a silane compound at a content of 0.01% by mass or more and 1% by mass or less, and the silane compound preferably contains an alkyl silicate or its oligomer, and a hydrolyzate or polymer of an organic silane compound. The concentration of the silane compound relative to the total mass of the metal treatment solution is more preferably 0.05% by mass or more and 0.5% by mass or less. The concentration of the silane compound can be adjusted based on the amount of the metal treatment solution to be applied to the surface of the metal substrate. Specifically, the silane compound contained in the metal treatment solution is preferably 0.005% by mass or more and less than 1% by mass of an alkyl silicate or its oligomer, and 0.005% by mass or more and less than 1% by mass of a hydrolyzate or polymer of an organic silane compound.

[0048] When the specific metal treatment solution as described above is applied to at least a part of the surface of a metal substrate, an alkyl silicate or its oligomer is introduced to the surface of the substrate, forming a composite oxide film of the metal and silicon that constitute the metal substrate. Then, in the subsequent drying process, a silane film made of an organic silane compound is formed in which the organic silane compound and the composite oxide film are chemically bonded. In this way, a surface-treated metal material can be obtained that has excellent bonding properties with adhesives, is very excellent in corrosion resistance, and is less likely to lose adhesive strength even when exposed to a high-temperature humid environment, and has excellent adhesive durability. In addition, when the metal treatment solution is used, surface treatment with an alkyl silicate or its oligomer and surface treatment with an organic silane compound can be performed in one step, so that a surface-treated metal material with excellent adhesive durability can be manufactured in a simplified process, and equipment investment and manufacturing costs can be reduced.

[0049] The pH of the metal treatment solution is preferably 2 or more and 7 or less. If the pH of the metal treatment solution is higher than 7, the alkyl silicate or its oligomer is likely to polymerize excessively, which is undesirable since the storage stability of the solution may decrease. In addition, as the polymerization of the alkyl silicate or its oligomer progresses, the film formed becomes thicker, and when stress is applied, destruction occurs inside the silane film, making it impossible to obtain high adhesive strength. Therefore, the pH of the metal treatment solution is preferably 7 or less, and more preferably 6 or less from the viewpoint of the stability of the alkyl silicate.

[0050] On the other hand, if the pH of the metal treatment solution is lower than 2, the surface of the substrate will be dissolved vigorously, and the coating will become non-uniform, making it difficult to achieve stable adhesive performance. Therefore, the pH of the metal treatment solution is preferably 2 or higher, and in consideration of the reactivity with the metal oxide coating, it is more preferably 3 or higher. The pH of the metal treatment solution can be appropriately adjusted by adding an acid such as hydrochloric acid, sulfuric acid, nitric acid, or acetic acid.

[0051] The concentration of the alkyl silicate or its oligomer in the metal treatment solution is preferably 0.005% by mass or more and less than 1% by mass. If the concentration of the alkyl silicate or its oligomer in the metal treatment solution is 1% by mass or more, the coating formed may become thick and its strength may decrease. Therefore, the concentration of the alkyl silicate or its oligomer in the metal treatment solution is preferably less than 1% by mass, more preferably less than 0.5% by mass, and even more preferably less than 0.2% by mass.

[0052] On the other hand, if the concentration of the alkyl silicate or its oligomer in the metal treatment solution is less than 0.005% by mass, the concentration of the alkyl silicate or its oligomer is too low, and therefore a composite oxide film of the metal and silicon constituting the metal substrate cannot be sufficiently formed, and sufficient adhesion durability may not be obtained. Therefore, the concentration of the alkyl silicate or its oligomer in the metal treatment solution is preferably 0.005% by mass or more, more preferably 0.01% by mass or more, and even more preferably 0.02% by mass or more.

[0053] In addition, the concentration of the organosilane compound in the metal treatment solution is preferably 0.005% by mass or more and less than 1% by mass. If the concentration of the organosilane compound in the metal treatment solution is 1% by mass or more, the coating film formed may become thick and its strength may decrease. In addition, the stability of the solution may also decrease. Therefore, the concentration of the organosilane compound in the metal treatment solution is preferably less than 1% by mass, more preferably less than 0.5% by mass, and even more preferably less than 0.2% by mass.

[0054] On the other hand, if the concentration of the organosilane compound in the metal treatment solution is less than 0.005% by mass, the concentration of the organosilane compound is too low, making it impossible to form a sufficient surface treatment film containing the organosilane compound, and sufficient adhesion durability cannot be obtained. Therefore, the concentration of the organosilane compound in the metal treatment solution is preferably 0.005% by mass or more, more preferably 0.01% by mass or more, and even more preferably 0.02% by mass or more.

[0055] When the mass of alkyl silicate or its oligomer contained as the silane compound in the metal treatment solution is X and the mass of the hydrolyzate or polymer of the organosilane compound is Y, the ratio of X to Y is preferably 4:1 to 1:4. Furthermore, the ratio of X to Y is more preferably 2:1 to 1:2. In order to control the polymerization of these substances and stabilize the metal treatment solution, the metal treatment solution preferably contains 1 mass % or less of an acid relative to the total mass of the silane compound.

[0056] In the silane film composed of an alkyl silicate or its oligomer and a hydrolyzate or polymer of an organic silane compound, it is preferable to adjust the film weight to an optimal range in order to exhibit sufficient adhesion durability. 2 If the amount of the silane coating is less than 20 mg / m, the metal surface cannot be sufficiently covered with the coating, and it may be difficult to obtain the desired adhesion durability. 2 If the thickness of the silane film exceeds 0.1 mg / m, the silane film becomes bulky, and the adhesion of the silane film to the metal substrate becomes insufficient, which may cause destruction starting from the silane film, making it difficult to obtain the desired adhesive strength. 2 More than 20mg / m 2 It is preferable to keep it below 0.5 mg / m 2 More than 15mg / m 2 It is more preferable that the ratio of X to Y in the metal treatment solution is designed to be within the above range to prepare the metal treatment solution, thereby making it possible to achieve a preferable coating amount of the silane coating.

[0057] The type of alkyl silicate or its oligomer contained in the metal treatment solution is not particularly limited, but silicate, tetraalkoxy orthosilicate or its oligomer is preferred from the viewpoint of not producing by-products that may cause corrosion of the film or deterioration of the adhesive resin after the reaction. Among them, it is preferred to use tetraethyl orthosilicate (TEOS) or its polymer (oligomer) because it is neutral and no alkali remains after the formation of the silane film. The polymer includes oligomers. Here, the alkyl silicate or its oligomer may be used alone or in combination of two or more kinds.

[0058] The type of organic silane compound contained in the metal treatment solution is not particularly limited, but the organic silane compound may contain a silane compound having a plurality of hydrolyzable trialkoxy groups in the molecule, its hydrolyzate, or its polymer. A silane compound having a plurality of hydrolyzable trialkoxy groups in the molecule not only forms a dense siloxane bond by self-polymerization, but also has high reactivity with metal oxides and forms a chemically stable bond, so that the durability of the silane film can be further improved. In addition, the silane film has high mutual solubility with machine oils such as processing oil and press oil, and organic compounds such as adhesives, and can mitigate the effect of machine oils such as processing oil and press oil on the film, so that it also plays a role in preventing the deterioration of adhesion durability due to oil application. The type of the silane compound is not particularly limited, but from the viewpoint of economic efficiency, a silane compound having two hydrolyzable trialkoxysilyl groups in the molecule (bissilane compound) is preferred, and for example, bistrialkoxysilylethane, bistrialkoxysilylbenzene, bistrialkoxysilylhexane, bistrialkoxysilylpropylamine, bistrialkoxysilylpropyltetrasulfide, etc. can be used. In particular, from the viewpoints of versatility, economic efficiency, and stability of the aqueous solution, it is preferable to use bistrialkoxysilylethane, and it is more preferable to use bistriethoxysilylethane (BTSE). Here, as the organic silane compound, only one type may be used alone, or two or more types may be used in combination.

[0059] In addition, the organic silane compound may contain a silane coupling agent having a reactive functional group capable of chemically bonding with an organic resin component, its hydrolyzate, or its polymer.For example, a silane coupling agent having a reactive functional group such as an amino group, an epoxy group, a methacryl group, a vinyl group, and a mercapto group can be used alone or in combination with a silane compound to form a chemical bond between the coating and the resin, thereby further improving the adhesion durability.The functional group of the silane coupling agent is not limited to the above-mentioned one, and a silane coupling agent having various functional groups can be appropriately selected and used according to the adhesive resin used. Suitable specific examples of the silane coupling agent include, for example, 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, 3-(N-aminoethyl)-aminopropyltrimethoxysilane, 3-(N-aminoethyl)-aminopropyltriethoxysilane, 3-mercaptopropyltrimethoxysilane, 3-mercaptopropyltriethoxysilane, 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropyltriethoxysilane, 3-methacryloxypropyltrimethoxysilane, 3-methacryloxypropyltriethoxysilane, etc. Here, as the silane coupling agent, only one kind may be used alone, or two or more kinds may be used in combination.

[0060] In this embodiment, if the metal treatment solution contains a particulate inorganic compound having a diameter of 10 nm or more (hereinafter, simply referred to as "particulate inorganic compound"), an additional process such as washing with water to remove the silane film is required after the silane film is formed. In addition, the silane film formed may become thick, which may reduce the adhesive strength and adhesive durability. Therefore, it is preferable that the metal treatment solution is substantially free of particulate inorganic compounds. Note that "the metal treatment solution is substantially free of particulate inorganic compounds" is not limited to an embodiment in which the particulate inorganic compound is not contained at all, and it is acceptable for the particulate inorganic compound to be contained at an impurity level. Specifically, it is acceptable for the particulate inorganic compound to be contained up to 0.05 mass % or less with respect to the total amount of the metal treatment solution. Examples of particulate inorganic compounds include sols of inorganic oxides such as silica and alumina. Note that the diameter of the particulate inorganic compound refers to the diameter measured by observing the solid content of the treatment solution after drying with a transmission electron microscope (TEM) or by measuring the diameter of the diluted treatment solution with a submerged particle counter.

[0061] In addition to the alkyl silicate or its oligomer, and the organic silane compound, the metal treatment solution may further contain, as necessary, one or more stabilizers, assistants, etc. For example, as a stabilizer, the solution may contain an organic compound such as a carboxylic acid having 1 to 4 carbon atoms, such as formic acid or acetic acid, or an alcohol having 1 to 4 carbon atoms, such as methanol or ethanol.

[0062] The method for preparing the metal treatment solution includes, but is not limited to, the following preparation method. First, an organic silane compound and a small amount of acetic acid as a catalyst are added to a mixture of alcohol such as ethanol and water, and the organic silane compound is sufficiently hydrolyzed to obtain an aqueous solution of the organic silane compound. Next, an aqueous solution of an alkyl silicate or its oligomer is prepared by the same method, and these two liquids are mixed, and then diluted with water to a predetermined concentration to prepare a metal treatment solution. In addition, since alkyl silicate or its oligomer is basic and easily polymerized, when a basic compound is used as the organic silane compound, it is preferable to neutralize the organic silane solution with acetic acid or the like in advance before preparing the solution in order to avoid excessive polymerization of the alkyl silicate or its oligomer when the solutions are mixed.

[0063] [zygote] The bonded body according to the present embodiment includes the above-mentioned surface-treated metal material. Specifically, the bonded body includes a first member and a second member bonded together via an adhesive resin layer. At least one of the first member and the second member may be the above-mentioned surface-treated metal material, and the silane coating of the surface-treated metal material is bonded to the adhesive resin layer.

[0064] The bonded body according to the present embodiment configured as described above is unlikely to lose adhesive strength even when exposed to a high-temperature humid environment, and has excellent adhesive durability. As described above, only one of the first member and the second member may be the surface-treated metal material according to the present invention, or both may be the surface-treated metal material according to the present invention. When only one of the first member (the first member) is a surface-treated metal material, The other member (second member) may be a metal material that has not been surface-treated, a resin molded body that has not been surface-treated, etc. As the metal material that has not been surface-treated, various metal materials such as titanium or titanium alloy material, aluminum or aluminum alloy material, copper or copper alloy material, stainless steel material, etc. may be used.

[0065] As the resin molded body, for example, a fiber-reinforced plastic molded body formed from various fiber-reinforced plastics such as glass fiber reinforced plastic (GFRP), carbon fiber reinforced plastic (CFRP), boron fiber reinforced plastic (BFRP), aramid fiber reinforced plastic (AFRP, KFRP), polyethylene fiber reinforced plastic (DFRP), and Zylon fiber reinforced plastic (ZFRP) can be used. By using these fiber-reinforced plastic molded bodies, it is possible to reduce the weight of the joined body while maintaining a certain level of strength.

[0066] In addition to the above-mentioned fiber-reinforced plastics, the resin molded body may also be made of non-fiber-reinforced engineering plastics such as polypropylene (PP), acrylic-butadiene-styrene copolymer (ABS) resin, polyurethane (PU), polyethylene (PE), polyvinyl chloride (PVC), nylon 6, nylon 6,6, polystyrene (PS), polyethylene terephthalate (PET), polyamide (PA), polyphenylene sulfide (PPS), polybutylene terephthalate (PBT), and polyphthalamide (PPA).

[0067] When both the first member and the second member are surface-treated metal materials according to the present invention, the types of metal substrates may be the same or different, and various combinations of metal substrates can be used.

[0068] [Method of manufacturing the bonded body] The bonded body according to the present embodiment can be manufactured by a conventional method. For example, an adhesive resin layer is formed by a conventional method in the region where the silane film is formed, and another member is bonded so as to be in contact with the adhesive resin layer. The method for forming the adhesive resin layer is not particularly limited, but as described above, an adhesive sheet made of an adhesive resin material may be used, or the adhesive resin material may be sprayed or applied to the surface of the silane film.

[0069] In the above-mentioned embodiment, an example of a surface-treated metal material on which an adhesive resin layer for manufacturing a joint body is formed is shown, but the present invention is not limited to the above-mentioned example, and may be a surface-treated metal material on which a coating film made of paint is formed on at least a part of the silane coating. In a surface-treated metal material on which a coating film is formed, the adhesion between the stainless steel base material and the silane coating is excellent, and the bonding between the silane coating and the paint is also excellent, so that it is possible to obtain the effect of preventing peeling of the paint. EXAMPLES

[0070] The present invention will be described in more detail below with reference to examples and comparative examples, but the present invention is not limited to these examples, and can be modified within the scope of the present invention, and all of these are included in the technical scope of the present invention. In addition, the various manufacturing conditions below are examples, and the present embodiment is not limited to the following conditions.

[0071] [Production of test materials] <Preparation of the substrate> First, plates made of various metal materials were cut to a length of 100 mm in the longitudinal direction and a width of 25 mm to prepare two metal substrates for each test condition. The types of metal materials are as follows: Aluminum alloy (JIS standard A7075): plate thickness 3.8 mm Aluminum alloy (JIS standard A5052): plate thickness 2 mm Pure titanium (JIS standard type 1): thickness 1.2 mm Stainless steel (JIS standard SUS304): Plate thickness 1mm

[0072] <Blast processing> Next, the evaluation range of the metal substrate was set to 10 mm from the longitudinal end and 25 mm in the width direction, and the substrates of invention examples 1 to 5 and comparative examples 4, 9 and 10 were subjected to dry or wet blasting treatment in the evaluation range, followed by rinsing with water for 1 minute. The treatment conditions for the blasting treatment were as follows. Comparative examples 1 to 3 and 5 to 8, which were not subjected to the blasting treatment, were only washed with acetone.

[0073] (Dry (Dry) Blasting Treatment Conditions) Dry Blasting Equipment: Shot Blasting Equipment (NAB-3K) manufactured by Nissan Kikai Co., Ltd. Abrasive Material: White Molybdenum Random Abrasive Grains manufactured by Showa Denko K.K.: WA#150 Blasting Pressure: 0.7 (MPa)

[0074] (Wet (Wet) Blasting Treatment Conditions) Wet Blasting Equipment: BABY BlastII (Model: MBBII-25) manufactured by Marco Co., Ltd. Abrasive Material: White Molybdenum Random Abrasive Grains manufactured by Showa Denko K.K.: WA#150, WA#320 Air Pressure: 0.12 MPa Gun Moving Speed: 10 mm / sec

[0075] <Formation of Silane Film> Thereafter, for the substrates of Invention Examples No. 1 to 5 and Comparative Examples No. 5 to 8, they were immersed in a metal treatment solution containing the following Silicon Compound 1 and Silicon Compound 2 at room temperature for 10 seconds, and then pulled out. Then, a silane film was produced by drying at a temperature of 100°C for 60 seconds in a blowing drying furnace to obtain test specimens.

[0076] (Metal Treatment Solution) Silicon Compound 1: Bis(triethoxysilyl)ethane (BTSE) 0.1 g Silicon Compound 2: Tetraethyl orthosilicate (TEOS) 0.1 g Ethanol 2.0 g Acetic Acid 0.001 g Water 97.8 g

[0077] [Measurement of the Surface of Test Specimens] <Measurement of Str (Aspect Ratio)> For the surface of each test material (the surface of the silane film), the surface roughness was measured using a laser microscope (KEYENCE VK-X150 / 160 shape analysis laser microscope) for a 1 mm × 1 mm measurement range at three arbitrary locations (Position 1, Position 2, and Position 3). As measurement conditions, the aspect ratio was measured with the magnification of the objective lens set to 20 times, and the average value of the three locations was calculated.

[0078] <Measurement of Absorption Spectrum by FT-IR> For the surface of each test material (the surface of the silane film), the absorption spectrum was measured using an FT-IR (Fourier transform infrared spectrometer: Nicolet Magna-750 spectrometer). Specifically, parallel polarized light with an incident angle of 75° was incident, and the absorption spectrum was measured. The presence or absence of absorption peaks in the wavenumber range of 1250 (cm -1 ) or higher and 1150 (cm -1 ) or lower was measured. For those with peaks, the absorbance was measured. The manufacturing conditions of the test materials, as well as the measurement results of the aspect ratio and absorbance, are shown in Table 1 below.

[0079] [Manufacture of Bonded Specimen] Subsequently, two test materials were joined with an adhesive to obtain a bonded specimen (bonded body). Figure 2A is a side view showing the shape of the bonded specimen, and Figure 2B is a plan view thereof. As shown in Figures 2A and 2B, an adhesive resin layer 35 was formed in the above evaluation range on the surface of the test material 31b (second member), and a test material 31a (first member) having the same configuration as the test material 31b was placed on top of this adhesive resin layer 35. The lap length was set to 10 mm, and the arrangement was made such that only the region 10 mm from the ends of the test material 31a and the test material 31b overlapped.

[0080] For invention examples No. 1 to 5 and comparative examples No. 5 to 8, since a silane film was formed in the above evaluation range, the 10 mm x 25 mm areas on which the silane film was formed were arranged with an adhesive resin layer 35 interposed between them. A structural thermosetting epoxy resin adhesive was used as the material for the adhesive resin layer. A small amount of glass beads (particle size 250 μm) was added to the adhesive resin material to adjust the thickness of the adhesive resin layer 35 to 250 μm. After being arranged in a stacked manner as described above, the pieces were dried at room temperature for 30 minutes, and further heated at 180°C for 30 minutes to perform a heat curing treatment. After that, the pieces were left to stand at room temperature for 24 hours to prepare a bonded test piece (bonded piece).

[0081] For Comparative Examples 1 to 3 and 5 to 8, the surfaces that had been cleaned with acetone were placed opposite each other with an adhesive resin layer 35 interposed therebetween, and bonded specimens were prepared in the same manner as above. For Comparative Examples 4, 9, and 10, the surfaces that had been blasted were placed opposite each other with an adhesive resin layer 35 interposed therebetween, and bonded specimens were prepared in the same manner as above.

[0082] [Evaluation of joint specimens] <Deterioration test> A degradation test was carried out on some of the obtained bonded specimens in order to evaluate the adhesive durability. The degradation test consisted of immersing the bonded specimens in a 5% NaCl solution at 40°C for the period shown in Table 1 below.

[0083] <Tensile test> A tensile test was carried out on the obtained bonded specimen to evaluate its adhesiveness. As a tensile condition, both ends of the bonded specimen were pulled in the tensile direction shown by the arrow in FIG. 2A at a tensile speed of 50 mm / min until it broke. Thereafter, the fracture surfaces of the surface-treated metal material 31a (first member) and the surface-treated metal material 31b (second member) were observed, and the area of ​​the region where interfacial peeling occurred between the surface-treated metal material 31a and the adhesive resin layer (interfacial peeling area of ​​the first member) and the area of ​​the contact surface between the surface-treated metal material 31a and the adhesive resin layer (adhesion area of ​​the first member) were measured. Similarly, the area of ​​the region where interfacial peeling occurred between the surface-treated metal material 31b and the adhesive resin layer (interfacial peeling area of ​​the second member) and the area of ​​the contact surface between the surface-treated metal material 31b and the adhesive resin layer (adhesion area of ​​the second member) were measured. Then, the cohesive failure rate was calculated by the following formula (2). The conditions of the deterioration test and the calculation results of the cohesive failure rate are shown in Table 1 below.

[0084] Cohesive failure rate (%) = 100 - {(interfacial peeling area of ​​the first component / adhesive area of ​​the first component) × 100 + (interfacial peeling area of ​​the second component / adhesive area of ​​the second component) × 100} (2)

[0085] [Table 1]

[0086] As shown in Table 1 above, inventive examples No. 1 to 5 are examples using specimens having a silane coating on the surface, and the average aspect ratio is within the range specified in the present invention, and the absorption peak is in a predetermined range, so that they showed excellent cohesive failure rates regardless of the type of substrate. In addition, even after immersion in a NaCl solution, they showed excellent cohesive failure rates, indicating that they have excellent adhesion durability.

[0087] On the other hand, in Comparative Example No. 1, a silane coating was not formed, the average aspect ratio was outside the range specified in the present invention, and no absorption peak existed within the specified range, so the cohesive failure rate after the deterioration test was low. In Comparative Example No. 2, a silane film was not formed and the average aspect ratio was outside the range specified in the present invention, so that the cohesive failure rate after the deterioration test was low. In Comparative Example No. 3, a silane film was not formed and there was no absorption peak in the specified range, so the cohesive failure rate was low even when immersion in the deterioration test was not performed. In Comparative Example No. 4, a silane film was not formed, and therefore no absorption peak was present in the prescribed range, and therefore the cohesive failure rate after the deterioration test was low.

[0088] Comparative Examples 5, 6 and 8 had a silane coating formed thereon and had an absorption peak in a specified range, but the average aspect ratio was outside the range specified in the present invention, and therefore the cohesive failure rate after the deterioration test was low. Comparative Example No. 7 had a silane coating formed thereon and had an absorption peak in a specified range, but since the average aspect ratio was outside the range specified in the present invention, the cohesive failure rate was low even when immersion in a degradation test was not performed. In Comparative Examples 9 and 10, the average aspect ratio was within the range specified by the present invention, but since a silane coating was not formed and no absorption peak existed in the specified range, the cohesive failure rate after the deterioration test was low. [Explanation of symbols]

[0089] 31a Surface-treated metal material (first component) 31b Surface-treated metal material (second component) 35 Adhesive resin layer

Claims

1. A surface-treated metal material having a silane coating on at least a part of a surface of a metal substrate, When parallel polarized light having an incident angle of 75° was incident on the surface of the silane coating, the absorption spectrum was measured by Fourier transform infrared spectroscopy, and the absorption spectrum was 1250 (cm -1 ) or more 1150 (cm -1 ) or less wave number region, A surface-treated metal material characterized in that, when the surface roughness of the surface of the silane coating is measured using a laser microscope over a measurement range of 1 mm x 1 mm at any three points on the surface of the silane coating, Str (aspect ratio of the surface characteristics) is 0.8 or more.

2. 2. The surface-treated metal material according to claim 1, further comprising an adhesive resin layer on the surface of the silane coating.

3. 2. The surface-treated metal material according to claim 1, wherein the absorbance at the absorption peak is 0.003 or more.

4. The surface-treated metal material described in claim 1, characterized in that the metal substrate is at least one of pure titanium, a titanium alloy, and stainless steel.

5. A joined body comprising the surface-treated metal material according to any one of claims 1 to 4, The first member and the second member are joined via an adhesive resin layer, One of the first member and the second member is the surface-treated metal material, A bonded body, characterized in that the silane coating of the surface-treated metal material and the adhesive resin layer are bonded to each other.

6. A joined body comprising the surface-treated metal material according to any one of claims 1 to 4, The first member and the second member are joined via an adhesive resin layer, the first member and the second member are both surface-treated metal materials each having the metal base material made of the same or different metal materials, A bonded body, characterized in that the silane coating of the first member and the silane coating of the second member are bonded to each other by the adhesive resin layer.

Citation Information

Patent Citations

  • surface treatment composition

    JP1998510307A

  • Aluminum alloy article, aluminum alloy member, and method for producing the same

    JP2013083005A

  • Underlayer treatment solution, method for manufacturing organic coated galvanized steel pipe using the same and organic coated galvanized steel pipe

    JP2016108629A

  • Metal surface treatment method, and utilization thereof

    JP2016211035A

  • Aqueous solution for metal surface treatment, treatment method of metal surface and conjugate

    JP2019085610A